Informing compliance factors regarding hospitals waste management procedures in Indonesia: a scoping review - Kaban, Markus; Soeprobowati, Tri Retnaningsih; Suhartono, Suhartono; Pireno, Purwanto Adi; Kristanti, Alberta Widya; Sebong, Perigrinus Hermin (Intelektual Pustaka Media Utama, 2025)
The hospital staff's non-compliance in managing hazardous waste can hurt the environment and public health. There are various practicals to mitigate the harmful effects of hazardous medical waste on the environment and public health. However, there needs to be evidence to provide accurate data regarding compliance with hazardous waste management at hospitals in Indonesia. This study aims to assess and map the determinants affecting hospital liquid medical waste management. This study examined electronic databases from 2017-2023. Studies were screened based on inclusion and exclusion criteria. The study was grounded in the scoping review to inform compliance factors regarding waste management in Hospitals. One article describes compliance with the regulation, and the other concerns supervising hospital waste management. Those articles are not detailed enough in describing supervision, so we suggest further research about supervision support to foster the management process and the result of hospital waste management. Regulation is essential for all processes and products that affect the environment. Compliance with guidelines needs to become a habit and improve over time.